Integrasi Teknologi dalam Pembelajaran Adaptif untuk Meningkatkan Kemampuan Menyimak Siswa - Nurhopipah, Siti; Ulfatullailah, Eneng; Latifah, Latifah; Sadat, Angwar; Alam, Najmial Syah; Zulfitria, Zulfitria (TSAQOFAH, 2025)
Listening is a fundamental language skill essential for effective comprehension and communication, and it must be mastered by students to support overall language learning. In the digital era, technology-based adaptive learning has emerged as an innovative approach capable of addressing individual learning needs in a more personalized manner. This article aims to theoretically and conceptually examine how the integration of technology into adaptive learning can enhance students’ listening skills. The method employed is a literature review with critical analysis of books, national and international journals, and other relevant sources. The findings indicate that the use of technologies such as adaptive learning applications, interactive media, and artificial intelligence has a significant impact on improving listening competence by tailoring instruction to students' individual learning styles, pace, and needs. These findings affirm that technology-based personalized learning not only increases student engagement but also strengthens the overall effectiveness of the listening instruction process. The implications of this review encourage the development of technology-oriented learning strategies aimed at reinforcing language skills, particularly listening within formal educational settings.